Historical Analysis of the Environmental Aspects of Maritime Security Issues in the Gulf of Guinea: An Examination of the Niger Delta Region, Nigeria. - Effiong, Eke Nta (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2025)
The historical background of environmental security issues and their effects on the Niger Delta region's maritime domain are examined in this paper. It examines how the environment of the area, particularly the water bodies, is affected over time by deforestation, open defecation, illegal and unprotected fishing, quarrymen's operations, oil spills, and gas flaring. The study employs a qualitative research approach, consulting secondary materials such as academic literature and official documents, in addition to primary sources, including field reports and interviews. According to the study's findings, the region's maritime environment faced several security issues, including open defecation, environmental degradation, and deforestation, which were exacerbated by the onset of oil extraction following its discovery in the 1950s. Since then, the region's maritime domain has faced increased security challenges. This study emphasizes the intricate dynamics underlying security issues and the necessity of sustainable development and environmental preservation to guarantee environmental security in the area by examining the interactions between these factors and maritime security difficulties.